Pengaruh Corporate Governance Terhadap Kualitas Environemtal Disclosure - Kholmi, Masiyah; Sumarji, Siti Aminah; Zubaidah, Siti (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2019)
This study aims to examine the effect of corporate governance on environmental disclosure quality in companies listed on the Indonesia Stock Exchange and become PROPER participant for the period 2017. The research sample numbered 25 with purposive sampling technique. Data collection techniques with secondary data. Data is taken in the form of published data on the official website of the Indonesia Stock Exchange. Data analysis uses Partial Least Square, While testing the hypothesis using the outer model and inner model. Based on the results of the study found corporate governance have a positive effect on environmental disclosure quality.